2010
DOI: 10.1248/bpb.33.535
|View full text |Cite
|
Sign up to set email alerts
|

A Common Origin: Signaling Similarities in the Regulation of the Circadian Clock and DNA Damage Responses

Abstract: INTRODUCTIONFrom bacteria to humans, almost all organisms can adapt the timing of their physiology to the cyclic changes of their environment, thanks to a naturally-selected intrinsic timekeeping system called the circadian clock. 1) The circadian clock enhances the physiological efficiency and survival of an organism by organizing its behavior and body functions. 2,3) During the circadian day, the organism's physiology is given over to catabolic processes, whereas the anabolic functions of growth, repair and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 123 publications
(176 reference statements)
0
55
1
3
Order By: Relevance
“…Once the PER and CRY proteins have been translated, they form heterodimers that can then translocate to the nucleus to repress CLOCK (NPAS2) : BMAL-mediated transcription through direct protein-protein interaction. These interactions then set up the rhythmic oscillations of gene expression that drive the circadian clock.Zebrafish have been established as an attractive vertebrate model suitable for the examination of the light signaling pathway and its impact on the circadian clock.5) Not only are the molecular components of the mammalian and zebrafish circadian oscillators highly similar, 5,6) but zebrafish clocks have the unusual attribute of being directly light-responsive. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Once the PER and CRY proteins have been translated, they form heterodimers that can then translocate to the nucleus to repress CLOCK (NPAS2) : BMAL-mediated transcription through direct protein-protein interaction. These interactions then set up the rhythmic oscillations of gene expression that drive the circadian clock.Zebrafish have been established as an attractive vertebrate model suitable for the examination of the light signaling pathway and its impact on the circadian clock.5) Not only are the molecular components of the mammalian and zebrafish circadian oscillators highly similar, 5,6) but zebrafish clocks have the unusual attribute of being directly light-responsive. …”
mentioning
confidence: 99%
“…6,12) Importantly, studies in zebrafish have revealed critical roles for the cellular redox state and mitogen activated protein kinase (MAPK) signaling pathways in the regulation of light-dependent gene expression. 5,10,13) In a variety of organisms, light induces ROS production that alters the reduction-oxidation (redox) state within cells. In zebrafish cells, a light-induced change in redox state stimulates intracellular extracellular signal-regulated kinase (ERK)/MAPK signaling that transduces photic signals.…”
mentioning
confidence: 99%
“…Essa é uma questão ainda muita debatida no meio científico, no qual vários candidatos são propostos para desempenhar o papel do fotopigmento circadiano em relógios periféricos de zebrafish. Dentre eles podemos destacar: (i) opsinas como teleost multiple tissue opsin (tmt-opsin) e a vertebrate ancient opsin (va-opsin); (ii) os criptocromos que, em drosófilas, são responsáveis pela fotorrecepção circadiana ; (iii) processos de estresse oxidativo através da ativação de oxidases contendo flavinas e produção de espécies reativas de oxigênio (ROS) (Uchida et al, 2010).…”
Section: Modelo De Estudo: Células Embrionárias Zem-2s De Danio Reriounclassified
“…A possível interação entre a via dos fosfoinositídeos e a via de AMPc/PKA foi avaliada em melanóforos de X. leavis (Isoldi et al, 2010 (Golombeck & Ralph, 1994;Golombeck & Ralph, 1995;Ding et al, 1994;Wanabe et al, 1995;Fukushima et al, 1997;Melo et al, 1997;Ferreyra et al, 1998;Agostino et al, 2004 (Gonzalez & Montminy, 1989), CaMK (Sheng et al, 1991) e MAPK (Xing et al, 1996). Os argumentos a favor da integração das vias de NO e MAPK vêm de estudos provando que a integridade dessas duas vias é essencial na fosforilação de CREB nos NSQs (Ding et al, 1994;Ding et al, 1997;Obrietan et al, 1999), e da demonstração de que a produção de NO é fundamental para a atividade de fosforilação das ERK em culturas primárias de córtex neural (Yun et al, 1998 (Hirayama et al, 2007;Uchida et al, 2010). Através desse sistema, o fóton absorvido por essas enzimas levaria à produção de espécies reativas de oxigênio (ROS), ativação da via das MAPKs e regulação dos genes de relógio, porém a participação efetiva dessas oxidases na fotorrecepção ainda não foi comprovada.…”
Section: Crosstalks Com a Via De Sinalização De Fosfoinositídeosunclassified
See 1 more Smart Citation